Regeneração in vitro de louro-pardo (Cordia trichotoma (Vellozo) Arrabida ex Steudel) - Nilton César Mantovani (Ciência Florestal, 2001)
This study was carried out aiming at evaluating the in vitro regeneration of louro-pardo (Cordia trichotoma (Vellozo) Arrabida ex Steudel). Nodal segments were desinfested and innoculated in two basal media: WPM (Wood Plant Médium, 1981) and MS (Murashige & Skoog, 1962) supplemented with BAP (6-Benzylaminopurine), TDZ (Thidiazuron), NAA (Naphthaleneacetic Acid), GA3 (Gibberellic Acid), IBA (Indole-3-Butyric Acid) and A.C. (Activated Charcoal) in different combinations and concentrations for each developmental step. The regeneration rate and the shoot elongation were higher in the WPM medium containing 0,1 mg.l-1 of BAP and GA3. The rooting of regenerated shoots was observed in IBA (0,5 mg.l-1) and Ativated Charcoal (1,5 g.l-1).